Guided portfolio writing as a scaffold for reflective learning in in-service contexts: a case study1. Issue 5 (19th October 2016) - Pires Pereira, Íris Susana; Cristo Parente, Maria Cristina; Vieira da Silva, Cristina
Abstract : Language is widely recognized as an inescapable mediating tool for professional learning, and with this text we want to contribute to a better understanding of the particular role that guided writing can play in in-service professional reflective learning. We analysed one pre-school teacher's written portfolio, the construction of which was guided to scaffold deep thinking about (and the transference of theory into) practice during participation in an in-service program about language education. Our case study shows that the writing process sustained robust learning about professional knowing, doing and learning itself: The teacher elaborated an integrative ethical understanding of the discussed theory, fully experienced newly informed practices and assessed her own learning by using theory to confront her previous knowledge and practices. Throughout the portfolio, the learning stance revealed by her voice varied accordingly. The study illustrates the potential of guided writing to scaffold reflective learning in in-service contexts.